2009
DOI: 10.1179/002032009x12536100262150
|View full text |Cite
|
Sign up to set email alerts
|

Radial and axial variation in specific gravity and anatomical properties of plantation grownEucalyptuscitriodoraHook

Abstract: Radial and axial variation in specific gravity and certain anatomical properties were investigated in twenty year old plantation grown Eucalyptus citriodora Hook. Specific gravity and certain anatomical properties varied significantly in both directions. Average specific gravity ranged from 0.666 to 0.711 pith outwards and 0.762 to 0.728 base upwards; average fibre length ranged from 1062 mm to 1301 mm and 1211 mm to 1166 mm in radial and axial directions respectively. Similarly vessel diameter showed a range … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 9 publications
(10 reference statements)
1
1
0
Order By: Relevance
“…Heartwood percentage in 20-year-old C. citriodora trees in India ranged from 74% to 84% at the trunk base (0.6 m) and 68% to 79% at the trunk top (6.6 m). In our study with 33-year-old trees, results showed that heartwood percentage in LV (70%) and LV (71%) soils is close to values found by the authors, regardless of height (Shashikala & Rao, 2009). We found a gradual increase in pith to bark direction for fiber length in three soil types.…”
Section: Anatomical Featuressupporting
confidence: 89%
“…Heartwood percentage in 20-year-old C. citriodora trees in India ranged from 74% to 84% at the trunk base (0.6 m) and 68% to 79% at the trunk top (6.6 m). In our study with 33-year-old trees, results showed that heartwood percentage in LV (70%) and LV (71%) soils is close to values found by the authors, regardless of height (Shashikala & Rao, 2009). We found a gradual increase in pith to bark direction for fiber length in three soil types.…”
Section: Anatomical Featuressupporting
confidence: 89%
“…In contrast, Quilhó et al (2006) found the fibre length of Eucalyptus grandis has an increasing trend from heartwood to sapwood. Shashikala and Vijendra (2009) revealed the significant differences of the cell dimension of Eucalyptus citriodora (Hook) from pith outward (heartwood to sapwood). The mean of fibre length and fibre diameter of Kawui wood can be classified as ‘medium.’ However, there is a significant difference between the ‘thick’ lumen diameter of Kawui wood and that of ‘medium’ lumen diameter of E. pellita (Lukmandaru 2016).…”
Section: Resultsmentioning
confidence: 99%